2016
DOI: 10.1016/j.jsxm.2016.11.317
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Clinical Tools for Vaginal and Vulvar Symptom Assessment in Cancer Patients and Survivors

Abstract: Introduction Healthcare professionals can play a pivotal role in promoting vulvovaginal health through assessment and appropriate intervention. Aim The development and validation of brief clinical measures to facilitate the identification of vulvovaginal symptoms in cancer patients/survivors is warranted. Methods 175 female cancer survivors attending a Female Sexual Medicine and Women’s Health Program from 9/26/2012–10/31/2014 completed the Vaginal Assessment Scale (VAS) and Vulvar Assessment Scale (VuAS)—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…49 studies reported on convergent validity of the FSFI-19 (Supplementary Table 3). The FSFI-19 was compared to measures measuring sexual function and satisfaction, 15,17,18,21,23e25,28,29,31,33,37,46,53,55,57,58,60,62,64,67e69,71, 72,74,78,79,92,93 quality of life, 19,92 mental health measures, 20,39 physical functional problems, 20,30,32,34,49,54,66,74,77,81,83,87 relationship quality, 20,39,52 and body image. 35,42,43,56,60 A full list of comparison measures can be found in Supplementary Table 3.…”
Section: Convergent Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…49 studies reported on convergent validity of the FSFI-19 (Supplementary Table 3). The FSFI-19 was compared to measures measuring sexual function and satisfaction, 15,17,18,21,23e25,28,29,31,33,37,46,53,55,57,58,60,62,64,67e69,71, 72,74,78,79,92,93 quality of life, 19,92 mental health measures, 20,39 physical functional problems, 20,30,32,34,49,54,66,74,77,81,83,87 relationship quality, 20,39,52 and body image. 35,42,43,56,60 A full list of comparison measures can be found in Supplementary Table 3.…”
Section: Convergent Validitymentioning
confidence: 99%
“…28 studies of "adequate" rating, 15,19,23,24,28e31,35,37,46,49,54e57,60, 66e69,71,72,74,77,78,81,87,93 2 studies of "doubtful" rating, 33,64 and 1 study of "inadequate" quality, 53 provided correlations rated as sufficient. 14 studies of "adequate" rating, 17,20,21,25,32,34,39,42,43,52,60,62,79,83 and 2 studies of "doubtful" rating, 58,92 provided correlations rated as insufficient. 1 study was rated as indeterminate, because not enough information was given for a reliable interpretation.…”
Section: Convergent Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical response was assessed using the Response Evaluation Criteria in Solid Tumors (RECIST) criteria 60 days after the procedure, as previously reported [ 15 ]. To assess the QoL before and after ECT, the following questionnaires were administered: (i) visual analog pain scale (VAS) [ 20 ]; (ii) EuroQol 5-Dimension 5-Level (EQ-5D-L5) [ 21 , 22 ]; (iii) Functional Assessment Of Cancer Therapy—Vulva cancer (FACT—V) [ 23 ]. FACT—V is a specific instrument used to assess the QoL during VC therapy.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire is composed of 15 specific items providing information on the QoL of patients treated for VC. Among the 15 items of FACT—V, for the purposes of the present analysis, we considered only the following four items as they appeared significantly modified in a previous study [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]: (i) I am bothered by discharge or bleeding from my vulva (“bleeding”); (ii) I am bothered by itching/burning in my vulva area (“burning”); (iii) I have discomfort when I urinate (“urination”); (iv) I have discomfort when I am sitting (“sitting”).…”
Section: Methodsmentioning
confidence: 99%